2020
DOI: 10.1002/cssc.202001242
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Lignin Coniferaldehyde Residues for Plant Properties and Sustainable Uses

Abstract: Increases in coniferaldehyde content, a minor lignin residue, significantly improves the sustainable use of plant biomass for feed, pulping, and biorefinery without affecting plant growth and yields. Herein, different analytical methods are compared and validated to distinguish coniferaldehyde from other lignin residues. It is shown that specific genetic pathways regulate amount, linkage, and position of coniferaldehyde within the lignin polymer for each cell type. This specific cellular regulation offers new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 59 publications
(206 reference statements)
3
29
0
Order By: Relevance
“…This assumption, based on the low substrate specificity of these different phenoloxidases when oxidising small phenolics in vitro, is effectively supported by the multitude of "non-canonical" constituents incorporated in lignin such as flavonoids (Lan et al, 2015) and hydroxystilbenes (del Río et al, 2017). However, these observations rarely differentiate between the cell walls of different cell types, as well as between their different cell wall layers, which exhibit drastically distinct monomeric composition, amount and structure of lignin (Terashima and Fukushima, 1988;Terashima et al, 2012;Blaschek et al, 2020a,b;Mottiar et al, 2020;Yamamoto et al, 2020). As cell wall lignification is a cell-cell cooperative process (Pesquet et al, 2013;Smith et al, 2013) mediated by the release of mobile lignin monomers in the apoplast, lignin formation in the specific cell wall layers of each cell type will require a directing force to control their distinct amount and composition, such as using different combinations of phenoloxidases.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption, based on the low substrate specificity of these different phenoloxidases when oxidising small phenolics in vitro, is effectively supported by the multitude of "non-canonical" constituents incorporated in lignin such as flavonoids (Lan et al, 2015) and hydroxystilbenes (del Río et al, 2017). However, these observations rarely differentiate between the cell walls of different cell types, as well as between their different cell wall layers, which exhibit drastically distinct monomeric composition, amount and structure of lignin (Terashima and Fukushima, 1988;Terashima et al, 2012;Blaschek et al, 2020a,b;Mottiar et al, 2020;Yamamoto et al, 2020). As cell wall lignification is a cell-cell cooperative process (Pesquet et al, 2013;Smith et al, 2013) mediated by the release of mobile lignin monomers in the apoplast, lignin formation in the specific cell wall layers of each cell type will require a directing force to control their distinct amount and composition, such as using different combinations of phenoloxidases.…”
Section: Discussionmentioning
confidence: 99%
“…6B-C and S7). We then used two A. thaliana mutants to investigate how stem mechanical properties were affected by changes in lignin composition and concentration, specifically in the residues affecting TE collapse: the fah1 mutant, devoid of S and instead accumulating G CHOH (Meyer et al 1998;Yamamoto et al 2020), and the cad4×cad5 mutant enriched in total and terminal G CHO (Blaschek, Champagne, et al 2020;Sibout et al 2005;Yamamoto et al 2020). Biochemical analyses showed minor changes in lignin amounts, lower in fah1 and cad4×cad5 compared to WT plants, but major changes in S/G and G CHO /G CHOH as well as terminal/total G CHO (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lignin residue diversity was however acquired several times convergently by different vascular plant genera during plant evolution (Weng et al 2008). We recently questioned this "random" concept by showing that different xylem cell types, and their morphotypes, accumulated lignin G CHO residues using cell-specific genetic, cooperative and oxidative processes Blaschek, Champagne, et al 2020;Yamamoto et al 2020). We also showed that post-mortem lignification of TEs occurs in multiple plant species (Pesquet et al 2010;Pesquet et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a functional group at the position 2 of the conjugated aldehyde system enriches chemistry of such derivatives and determines fields of their application. Some 2-functionally substituted alkenals are plant and animal metabolites [ 4 , 5 , 6 , 7 , 8 ]. In industry, α-substituted α,β-unsaturated aldehydes are used as the starting materials in the production of dyes, pesticides, aromatic compounds, and drugs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%